The Stringent Support Requirements for Independent Candidates in Regional Elections: A Legal Self-Critique of Indonesian Democracy: Besarnya Syarat Dukungan Calon Independen dalam Pilkada: Auto Kritik Hukum terhadap Demokrasi Indonesia - Prasetyo, Yogi (Jurnal Konstitusi, 2024)
Local Election is considered not to reflect democracy, there are still obstacles in the form of a large percentage of support requirements that make it difficult for independent candidates. Responding to these problems, this study aims to explain the large percentage of support requirements that are burdensome for independent candidates and the importance of independent candidates in the local election. The research method used is literature study with a legal philosophy approach. The data are literature literacy materials related to the research theme. The results showed that the percentage of support for independent candidates in the local election was considered too large. So that it hinders and makes independent candidates unable to become candidates in the elections. This kills the life of democracy that is being built by Indonesia. Whereas the existence of independent candidates is important as a counterweight and a new color giver in the political saturation of the old ways that do not produce quality leaders. It is necessary to change the percentage of support for independent candidates so as not to hinder democracy.